Comprehensive review on carbon nanotubes embedded in different metal and polymer matrix: fabrications and applications. Issue 6 (2nd November 2022) - Khan, Fahad Saleem Ahmed; Mubarak, N. M.; Khalid, Mohammad; Khan, Mohammad Mansoob; Tan, Yie Hua; Walvekar, Rashmi; Abdullah, E. C.; Karri, Rama Rao; Rahman, Muhammad Ekhlasur
Abstract: Carbonaceous material, especially carbon nanotubes (CNTs), have incredible properties, such as high thermal and mechanical stabilities, good catalytic and adsorption capabilities. In recent years, hybrid nanocomposites have attained considerable attention, due to the combination of unique organic and inorganic elements in a single material. Hence, these nanocomposites have been employed for various applications, such as drug delivery, sensors, corrosion protection materials, flame retardant additives, and pollutant adsorbent. These nanocomposites can be fabricated through various approaches that include powder metallurgy, solution processing, reaction processing, melt processing, electrochemical, and many more. This present review mainly summarizes the various techniques for the fabrication, separation, and purification of CNTs and their nanocomposites, especially CNTs-based polymer and CNTs-based metals/metal oxides nanocomposites. Besides, effects of CNTs embedded with polymers (such as polypyrrole, poly-aniline, and poly-thiophene, etc.) and metals/metal oxides (such as manganese oxide (MnO2 ), copper (Cu), gold (Au), platinum (Pt), etc.) and how they can be employed toward innovative devices with fascinating properties for a broad range of applications are thoroughly discussed. Further, , industrial applications of CNTs-based polymer/ metal/metal oxides nanocomposites have been reviewed and discussed.